2010
DOI: 10.1055/s-0030-1249829
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Muscle Strength after Thoracotomy: Standard vs. Muscle-Sparing Posterolateral Thoracotomy

Abstract: For the preservation of muscle strength, especially in patients whose jobs involved manual work, muscle-sparing posterolateral thoracotomy should be the first choice rather than conventional thoracotomy. Moreover, if necessary, the latissimus dorsi muscle can be used more extensively as a flap after muscle-sparing posterolateral thoracotomy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
12
1
1
Order By: Relevance
“…[18] Physiologic studies demonstrate improvements in maximal inspiratory/expiratory pressure at three months, lesser degrees of intercostal nerve impairment and improved shoulder function with muscle sparing techniques. [14], [19], [20] Prospective studies comparing muscle sparing and muscle splitting thoracotomies did not find differences in immediate or longer term post-operative pain or physical function. [19], [21] Notably adequate epidural anesthesia was provided in these trials.…”
Section: Current Practicementioning
confidence: 91%
See 2 more Smart Citations
“…[18] Physiologic studies demonstrate improvements in maximal inspiratory/expiratory pressure at three months, lesser degrees of intercostal nerve impairment and improved shoulder function with muscle sparing techniques. [14], [19], [20] Prospective studies comparing muscle sparing and muscle splitting thoracotomies did not find differences in immediate or longer term post-operative pain or physical function. [19], [21] Notably adequate epidural anesthesia was provided in these trials.…”
Section: Current Practicementioning
confidence: 91%
“…[12] A myriad of thoracic incisions developed, the widely used posterolateral thoracotomy has been modified to decrease the length, reduce the amount of muscle disrupted and protect the intercostal nerves all with varying amounts of patient benefit in terms of improved pain control, lung function and shoulder strength. [13], [14] Alternative incisions include the sternotomy, the clamshell incision, axillary and anterior thoracotomies. Median sternotomy allows access to the majority of both thoracic cavities.…”
Section: Current Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies advocating the MST approach have shown that compared with a PLT, patients experienced less postoperative pain, improved shoulder strength and mobility, and demonstrated better preservation of lung function. [6][7][8][9][10][11][12] However, other studies showed no significant differences in these outcomes when comparing the 2 surgical techniques. 1,[13][14][15][16][17] Critics of the MST technique imply that differences in outcomes are not clinically significant or can be attributed to advancements in surgical techniques and anesthesia.…”
Section: Introductionmentioning
confidence: 96%
“…[29][30][31][32][33] The LD muscle, when preserved, can solely provide adequate reach and bulk of vascularized tissue to address most postlobectomy complications. Although the importance of preservation of the extrathoracic chest muscles for rotational flaps in the event of a postresectional complication has been emphasized in numerous other studies, 1,2,11,12,14,17,34,35 the MST is still not widely utilized. When the LD muscle has been divided, another reconstructive flap option is the serratus anterior muscle.…”
Section: Introductionmentioning
confidence: 99%